2022
DOI: 10.3389/fnagi.2022.984075
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of lower extremity muscle strength on the relationship between mobility and cognitive function in Chinese older adults: A cross-sectional study

Abstract: Aging is a multifactorial process associated with irreversible decline in mobility and cognitive function. However, the mechanisms underlying the relationship between mobility and cognitive function remain elusive. In specific, the mediating effect of muscle strength, which is essential to maintain mobility, on this relationship has yet to be clarified. Accordingly, we performed a cross-sectional study involving Chinese older adults to understand the role of muscle strength in the relationship between mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Concerning the single-dimensional aspects of sarcopenia (i.e., reduced muscle mass and muscle strength), we did not find significant differences in the muscle mass metrics considered by sarcopenia diagnostic criteria (i.e., SMI, ASM and ASM/height 2 ) between AD patients and controls. Conversely, handgrip strength was significantly lower in AD patients compared to controls, consistent with findings from previous studies [19,27]. Finally, we found that the MQI was lower in AD patients than in controls but showed poor diagnostic accuracy (AUC ranging between 0.35 and 0.53) in identifying sarcopenia cases, regardless of the diagnostic criteria adopted.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the single-dimensional aspects of sarcopenia (i.e., reduced muscle mass and muscle strength), we did not find significant differences in the muscle mass metrics considered by sarcopenia diagnostic criteria (i.e., SMI, ASM and ASM/height 2 ) between AD patients and controls. Conversely, handgrip strength was significantly lower in AD patients compared to controls, consistent with findings from previous studies [19,27]. Finally, we found that the MQI was lower in AD patients than in controls but showed poor diagnostic accuracy (AUC ranging between 0.35 and 0.53) in identifying sarcopenia cases, regardless of the diagnostic criteria adopted.…”
Section: Discussionsupporting
confidence: 90%